2020
DOI: 10.3233/jad-200229
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation with Matured Hop Bitter Acids Improves Cognitive Performance and Mood State in Healthy Older Adults with Subjective Cognitive Decline

Abstract: Background: Prevention of age-related cognitive decline and depression is becoming urgent because of rapid growing aging populations. Effects of vagal nerve activation on brain function by food ingredients are inadequately investigated; matured hop bitter acid (MHBA) administration reportedly improves cognitive function and depression via vagal nerve activation in model mice. Objective: We investigated the effects of MHBA supplementation on cognitive function and mood s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 50 publications
0
10
0
1
Order By: Relevance
“…Treatment improved verbal memory and executive function compared to participants in the placebo group [82]. The same supplement was tested in 49 adults (45-69 years), increasing the Symbol Digit Modalities Test score and also memory retrieval in the subgroup with SCD [83]. The effect of low (600 mg/d, n = 30) and high-doses (1200 mg/d, n = 30) of Tremella fuciformis (TF) consumption on cognition was evaluated in 60 young adults after 4 and 8 weeks of intervention, and subjects in the intervention group showed fewer self-reported cognitive complaints, better short-memory and executive functions compared to placebo in a non-dependent dose manner.…”
Section: Other Types Of Dietary Supplements (N = 15)mentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment improved verbal memory and executive function compared to participants in the placebo group [82]. The same supplement was tested in 49 adults (45-69 years), increasing the Symbol Digit Modalities Test score and also memory retrieval in the subgroup with SCD [83]. The effect of low (600 mg/d, n = 30) and high-doses (1200 mg/d, n = 30) of Tremella fuciformis (TF) consumption on cognition was evaluated in 60 young adults after 4 and 8 weeks of intervention, and subjects in the intervention group showed fewer self-reported cognitive complaints, better short-memory and executive functions compared to placebo in a non-dependent dose manner.…”
Section: Other Types Of Dietary Supplements (N = 15)mentioning
confidence: 99%
“…Other dietary supplements that have shown significant improvements on different cognitive domains are fungi and algae extracts (Hericiumerinaceus, Tremella fuciformis and Laminaria japonica), other plant extracts (Eleutherococcussenticosus leaf, Drynariafortuneirhizome, combined sage, rosemary and melissa, auraptene, astaxanthin and matured hop bitter acids), minerals such as magnesium, medium-chain triglycerides and the complex Twendee X (supplement containing a mix of eight antioxidants). The consumption of the above antioxidant and anti-inflammatory supplements not only significantly improved subjective memory complaints [84] and scores in different cognitive domains such as psychomotor and processing speed [73], working memory [76,77,79,81], short-term memory [74,76,77,84], spatial working memory [75,79,81,87], verbal episodic memory [78], verbal fluency [75,82,83], language [75,79,81,87], executive functions [79,82,84] and attention [79,83,87], but also cortical gray matter integrity in AD-related brain regions [84]. The spermidine-rich plant extract also had an impact on memory performance in subjects with SCD, although this was not significant, probably due to the small sample size (n = 30) and/or the short follow-up period (3 months) [85].…”
Section: Other Types Of Dietary Supplementsmentioning
confidence: 99%
“…It is not advisable to take excessive drinking in daily life, as for the heavy alcohol drinkers, extracellular coldinducible RNA-binding protein (eCIRP) might mediate tau phosphorylation, leading to the progression of alcohol-induced AD (91). After matured hop bitter acid supplementation from beer, improvement of cognitive status was confirmed in a randomized trial (92). Particularly, alcohol from wine appeared to be stronger inversely related to the risk of dementia (89,90), polyphenolic and antioxidant contents in wine showed greater protective effects against neurodegeneration (93).…”
Section: Alcohol Consumptionmentioning
confidence: 99%
“…In a randomized double-blind placebo-controlled study in healthy adults, it was observed that the consumption of matured hop bitter acids (35 mg/day for 12 weeks) improved mental fatigue, mood state, verbal memory retrieval, and anxiety when compared with the placebo group (45-64 years) [115]. Indeed, hop bitter acids improved cognitive function, attention, and mood state in older people (45-69 years) with subjective cognitive decline [116].…”
Section: Hop Derivatives and Neuroprotectionmentioning
confidence: 99%